Formation and Effect of Deposited Thin TiO2 Layer With Compressive Strain and Oxygen Vacancies on GaAs (001) Substrate - Li, Yue; Zhou, Yunxia; Deng, Yanrong; Ta, Shiwo; Yang, Zhao; Li, Haiou; Sun, Tangyou; Chen, Yonghe; Zhang, Fabi; Fu, Tao; Wangyang, Peihua; Zhu, Jun; et al. (Frontiers in Materials, 2022)
The integration of metal oxides and GaAs semiconductors is quite attractive for its potential applications, but interfacial diffusion and lattice mismatch usually cause huge challenges towards achieving high-performance electronic devices. In this paper, we reported a thin layer of epitaxial TiO2 (110) on a GaAs (001) substrate with significant compressive strain, lattice distortion, and oxygen vacancies, where the oxygen vacancies proved to be the critical factor to induce the compressive strain and lattice distortion. In this case, the lattice mismatches between this compressed TiO2 (110) and GaAs (001) surface were calculated to be as small as 1.3% and 0.24% along the [110] and [001] orientations of TiO2, respectively. Further, no Ga-oxides or As-oxides were found at the interface, indicating that the TiO2 layer inhibited the diffusion of Ga and As atoms effectively. In summary, TiO2 film can be grown epitaxially on GaAs (001) substrates with nonnegligible compressive strain, lattice distortion, oxygen vacancies, and a high-quality interface. This study also provides an approach to integrate different functional oxides on TiO2-buffered GaAs for various GaAs-based electronic devices with higher reliability and performance.